Faktor-Faktor Internal dan Ekternal yang Mempengaruhi Kinerja Penyuluh Pertanian di Kabupaten Sumedang (Suatu Kasus di Kabupaten Sumedang) - Edang Juliana; Nataliningsih Nataliningsih (Jurnal Agristan, 2022)
ABSTRACTThis research was conducted in Sumedang Regency. This study aims to determine the internal and external factors that affect the performance of agricultural extension agents in Sumedang Regency.The method used in this research is the survey method (quantitative) with a combination of quantitative and qualitative approaches. Sampling was carried out by means of probability simple random sampling and there were 88 agricultural extension workers. The collected data were analyzed using SEM (Structural Equation Models) analysis. The results showed that:1). Simultaneously, internal and external factors have an effect on the performance of agricultural extension workers. It can be seen from the structural model (t-values) that internal factors (X1) are 2.45 and external factors (X2) are 2.59 which means X1 and X2 is greater than t-table 1.96.2). Internally, internal factors have no effect on the performance of agricultural instructors, seen from the t-hiting is smaller than t-table (1.01 1.96)3). Varially, external factors have an influence on the performance of agricultural extension workers, seen from the t-count is greater than the t-table (3.37 1.96).